2004
DOI: 10.4173/mic.2004.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vivo method for determining material properties of passive myocardium

Abstract: Calculation of mechanical stresses and strains in the left ventricular (LV) myocardium by the finite element (FE) method relies on adequate knowledge of the material properties of myocardial tissue. In this paper we present a model-based estimation procedure to characterize the stress-strain relationship in passive LV myocardium. A 3D FE model of the LV myocardium was used, which included morphological fiber and sheet structure and a nonlinear orthotropic constitutive law with different stiffness in the fiber,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The inverse problem itself can be solved by using a variety of methods and many studies have demonstrated that it is possible to estimate constitutive material parameters by using in vivo measurements even with very complex constitutive relations (Guccione et al, 1991;Remme et al, 2004;Sermesant et al, 2006;Sun et al, 2009). However, because of the strong correlation between the material parameters and sparse noisy data, the formulated inverse problem is highly non-linear (Xi et al, 2011;Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inverse problem itself can be solved by using a variety of methods and many studies have demonstrated that it is possible to estimate constitutive material parameters by using in vivo measurements even with very complex constitutive relations (Guccione et al, 1991;Remme et al, 2004;Sermesant et al, 2006;Sun et al, 2009). However, because of the strong correlation between the material parameters and sparse noisy data, the formulated inverse problem is highly non-linear (Xi et al, 2011;Gao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The model is equipped with two sets of fiber and sheet arrangements. In the first arrangement, a generic rulebased dataset is used where fiber/sheet angles vary linearly in the transmural direction, as seen previously in, e.g., [1,[7][8][9][10][11][12][13][14][15]. Several values for the linear change of fiber/sheet angles are examined.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the myocardial material properties is still an active ongoing research topic (Remme et al, 2004;Sommer et al, 2015). Although the myocardial tissue appears to be viscoelastic (Taber, 1995), the short cardiac cycle time scale compared to the tissue relaxation time makes it less significant to be simulated as a viscoelastic material.…”
Section: Appendix G Additional Related Workmentioning
confidence: 99%